2019
DOI: 10.1080/15592294.2018.1564426
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation and transcriptomic profiles in the lifestyle strategies and asexual development of the forest fungal pathogen Heterobasidion parviporum

Abstract: Heterobasidion parviporum is the most devastating fungal pathogen of conifer forests in Northern Europe. The fungus has dual life strategies, necrotrophy on living trees and saprotrophy on dead woods. DNA cytosine methylation is an important epigenetic modification in eukaryotic organisms. Our presumption is that the lifestyle transition and asexual development in H. parviporum could be driven by epigenetic effects. Involvements of DNA methylation in the regulation of aforementioned processes have never been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…According to the methylation data from more than 40 fungal species, most methylated cytosine bases exist in transcriptionally silent and repetitive loci, and they are absent in transcriptionally activated genes, indicating that fungal DNA methylation preferentially contributes to TE suppression for maintaining the genome integrity [58]. Analysis of genomic DNA methylation patterns confirmed that TEs are heavily methylated in both CpG (>90%) and nonCpG (>20%) sites in different developmental stages, and only a few TEs are expressed in H. parviporum [71]. Analogously, 5mC sites in mycelia are not evenly distributed but clustered across chromosomes, forming densely methylated domains around TE-rich and gene-poor regions [6,44].…”
Section: Patterns Of Dna Methylation In Fungal Plant Pathogensmentioning
confidence: 89%
See 4 more Smart Citations
“…According to the methylation data from more than 40 fungal species, most methylated cytosine bases exist in transcriptionally silent and repetitive loci, and they are absent in transcriptionally activated genes, indicating that fungal DNA methylation preferentially contributes to TE suppression for maintaining the genome integrity [58]. Analysis of genomic DNA methylation patterns confirmed that TEs are heavily methylated in both CpG (>90%) and nonCpG (>20%) sites in different developmental stages, and only a few TEs are expressed in H. parviporum [71]. Analogously, 5mC sites in mycelia are not evenly distributed but clustered across chromosomes, forming densely methylated domains around TE-rich and gene-poor regions [6,44].…”
Section: Patterns Of Dna Methylation In Fungal Plant Pathogensmentioning
confidence: 89%
“…In contrast, CG-enriched genes in fungi do not exhibit the same normal-like distribution of CG methylation across the gene body as plants and some insect species [58,74]. The methylation levels of transcribed genes in the CpG context are lower than in their flanking regions in H. parviporum [71]. In addition to methylation in TEs, approximately 20% of nonTE genes are also methylated in the mycelia of M. oryzae [44].…”
Section: Patterns Of Dna Methylation In Fungal Plant Pathogensmentioning
confidence: 93%
See 3 more Smart Citations